2006
DOI: 10.1038/sj.cdd.4401970
|View full text |Cite
|
Sign up to set email alerts
|

A novel cellular survival factor – the B2 subunit of vacuolar H+-ATPase inhibits apoptosis

Abstract: The ubiquitous vacuolar H þ -ATPase, a multisubunit proton pump, is essential for intraorganellar acidification. Disruption of its function leads to disturbances of organelle function and cell death. Here, we report that overexpression of the B2 subunit of the H þ -ATPase inhibits apoptosis. This antiapoptotic effect is not mediated by an increase in H þ -ATPase activity but through activation of the Ras-mitogen-activated protein kinase (MAPK)-signaling pathway that results in the serine phosphorylation of Bad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
(32 reference statements)
0
17
0
Order By: Relevance
“…It is reported that free unassembled subunits of the V-ATPase exist in a dynamic balance between the assembled and unassembled forms in cells (31). The free unassembled subunits of this enzyme play other functional roles, such as in cell differentiation, proliferation, and cell death, in addition to forming the enzyme complex for proton transport (18,19,25). Our previous report showed that the B2 subunit has an additional antiapoptotic effect, which is not mediated by an increase in V-ATPase activity but through activation of the Ras-MAPK signaling pathway that results in the serine phosphorylation of Bad residues 112 and 155 (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported that free unassembled subunits of the V-ATPase exist in a dynamic balance between the assembled and unassembled forms in cells (31). The free unassembled subunits of this enzyme play other functional roles, such as in cell differentiation, proliferation, and cell death, in addition to forming the enzyme complex for proton transport (18,19,25). Our previous report showed that the B2 subunit has an additional antiapoptotic effect, which is not mediated by an increase in V-ATPase activity but through activation of the Ras-MAPK signaling pathway that results in the serine phosphorylation of Bad residues 112 and 155 (19).…”
Section: Discussionmentioning
confidence: 99%
“…The free unassembled subunits of this enzyme play other functional roles, such as in cell differentiation, proliferation, and cell death, in addition to forming the enzyme complex for proton transport (18,19,25). Our previous report showed that the B2 subunit has an additional antiapoptotic effect, which is not mediated by an increase in V-ATPase activity but through activation of the Ras-MAPK signaling pathway that results in the serine phosphorylation of Bad residues 112 and 155 (19). Lee et al (18) revealed that the B2 subunit could be upregulated independently of the other subunits by increased transcription of a novel factor through an AP-2 site during monocytic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normal vH ϩ -ATPase activity has been shown to be essential for cell proliferation, growth, viability, and survival (20,23,29,30,47,53), and increasing evidence suggests that the pump is a main component of signal transduction pathways regulating these processes. Dechant et al (7) identified the vH ϩ -ATPase as a sensor of pH i changes and novel activator of PKA in response to glucose uptake and phosphorylation.…”
mentioning
confidence: 99%